The Use of Ginger Extract as a Diuretic in Multi-Slice Computed Tomography Urology Examinations at Dr. Moewardi General Hospital - Putri Hasna Azizah Salsabila; Ari Suwondo; Jeffri Ardiyanto; Gatot Murti Wibowo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Urological examinations using Multi Slice Computed Tomography (MSCT) often require the use of diuretic agents to enhance the visualization of the urinary tract system. However, the use of synthetic pharmacological agents may sometimes lead to undesirable side effects. The aim of this study was to evaluate the effectiveness of ginger extract (Zingiber officinale) as a natural diuretic alternative in MSCT urological examinations. This research utilized an experimental design, comparing two groups: one that was given ginger extract before the examination and another control group that did not receive any additional treatment. Key parameters observed included the degree of urinary tract distension, MSCT image quality, and the smoothness of contrast media excretion. The results indicated that the administration of ginger extract significantly increased the degree of ureteral and urinary bladder distension, leading to improved image visualization quality compared to the control group. These findings suggest that ginger extract can serve as a promising natural diuretic alternative for MSCT urological examinations. However, further studies with larger sample sizes are necessary to confirm the validity and reproducibility of these results. Ginger extract offers an innovative and potentially safer approach to improving the effectiveness of MSCT scans without the side effects associated with synthetic diuretics.